2018
DOI: 10.1080/03009742.2018.1450892
|View full text |Cite
|
Sign up to set email alerts
|

Associations of circulating cell-free microRNA with vasculopathy and vascular events in systemic lupus erythematosus patients

Abstract: In this cross-sectional study, the circulating miRNA profile distinguished SLE patients with atherosclerosis from those without. Furthermore, an eight-miRNA signature was associated with thrombocytopenia, venous thrombotic events, and β-glycoprotein I antibodies in SLE patients. Prospective studies are needed to confirm the findings and to establish the precise role of circulating miRNA profiling in the evaluation of atherosclerosis in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…For the observation of different miRNAs profiles in a subset of lupus patients who had cardiovascular events, Kay et al identified that miR-101, miR-375 and miR-125b were indicative of atherosclerosis, with a sensitivity of 86% and a specificity of 88%. They also found an eight-miRNA profile that differentiated a subgroup of SLE with venous thrombotic events, thrombocytopenia and β2-glycoprotein I antibodies [89]. Recently, the miRNA profile was assessed in SLE pDCs, APS secondary to SLE (SLE + APS) and primary APS (PAPS) patients, but the result showed that the whole miRNA profiles of SLE, SLE + APS and PAPS did not show any difference, as well as IFN score among the three groups [90], so the detailed role of miRNA in SLE cardiovascular events needs further investigation.…”
Section: Extracellular Rna and Organ Involvement In Slementioning
confidence: 94%
“…For the observation of different miRNAs profiles in a subset of lupus patients who had cardiovascular events, Kay et al identified that miR-101, miR-375 and miR-125b were indicative of atherosclerosis, with a sensitivity of 86% and a specificity of 88%. They also found an eight-miRNA profile that differentiated a subgroup of SLE with venous thrombotic events, thrombocytopenia and β2-glycoprotein I antibodies [89]. Recently, the miRNA profile was assessed in SLE pDCs, APS secondary to SLE (SLE + APS) and primary APS (PAPS) patients, but the result showed that the whole miRNA profiles of SLE, SLE + APS and PAPS did not show any difference, as well as IFN score among the three groups [90], so the detailed role of miRNA in SLE cardiovascular events needs further investigation.…”
Section: Extracellular Rna and Organ Involvement In Slementioning
confidence: 94%
“…MiR‐125b is no exception in this perspective. During our systematic literature search, we identified 12 articles examining the diagnostic utility of miR‐125b in different types of cardiovascular diseases, with the first report published 5 years ago (Table ) . Among these diseases, we found that coronary artery disease/coronary events (n = 4) and acute stroke (n = 3) are the most common diseases in which the role of circulating miR‐125b has been investigated, followed by intracranial aneurysms (n = 2), abdominal aortic aneurysm (n = 1), heart failure (n = 1) and VC (n = 1) (Table ).…”
Section: Microrna‐125b: a Potential Biomarker For Vascular Diseasesmentioning
confidence: 99%
“…A total of 158 published articles were retrieved during the study period. After applying the exclusion criteria, 35 articles were finally included with full text reviewed (Figure ) . If aligned based on the date of publication, it was observed that the number of studies addressing miR‐125b and vascular diseases increases gradually over time since the first report that was published in 2010 (Figure ).…”
Section: Microrna‐125b In Vascular Diseasesmentioning
confidence: 99%
“…They found that miR-31 was expressed lower while miR-21 is expressed higher in SLE, suggesting a significant association between miR-21/miR-31 balance and their impact on tuning the IL-2 pathway of T cell activation in SLE. Kay et al [114] reported three decreased cell-free circulatory miRs, miR-125b, miR-101, and miR-375, which were indicative of atherosclerosis.…”
Section: An Abnormal Cell-free Ncrna Expression In Slementioning
confidence: 99%